N-REL: A comprehensive framework of social media marketing strategic actions for marketing organizations - Artha Sejati Ananda; Ángel Hernández-García; Lucio Lamberti (Journal of Innovation & Knowledge (JIK), 2016)
Despite the increasing and ubiquitous use of social media for business activities, scholar research on social media marketing strategy is scant and companies deploy their social media marketing strategies guided by intuition or trial and error. This study proposes a comprehensive framework that identifies and classifies social media marketing strategic actions. The conceptual framework covers actions that support both transactional and relationship marketing. This research also positions social media marketing strategy and strategic actions in the context of the marketing organization theory, and discusses the impact of the incorporation of social media on the concept of marketing organization. The study offers valuable theoretical insight on social media marketing actions and the deployment of social media marketing strategies in companies. The investigation also provides hints about how to maximize the benefits from social media marketing for customer-oriented, market-driven organizations.
Keywords: M10; M15; M19; 650; Social media; Social media marketing; Marketing strategy; Marketing organization; Marketing organization theory; N-REL; Social media marketing actions